AUTOMATIC AND SEMI-AUTOMATIC PROCESSES OF WORDSMITH 3.0 AS A TEXTBOOK EVALUATION INSTRUMENT: A CASE STUDY - Jayakaran Mukundan; Anealka Aziz Hussin (TEFLIN, 2006)
As checklists developed for textbook evaluation are question-able in terms of reliability and validity, other ways are being sought to bring about more systematic, efficient and objective evaluation instruments, which can provide greater insight into the strengths and weak-nesses of textbooks. With this in mind, the researchers explored the abilities of WordSmith 3.0, a concordance software, in providing some insights into the structure of textbooks. This study will provide findings on data WordSmith 3.0 generates automatically and semi-automatically, and how this information could be used in the evaluation of textbooks.